The Effectiveness of Social Media Marketing Activities in Building Brand Equity and Patient Trust and its Influence on Visit Intention in Private Hospitals - Nabila Mu’taz Dzakiyya; Sri Rahayu Hijrah Hati (Journal La Sociale, 2024)
Technological developments and increasingly fierce competition for private hospitals have forced private hospitals to innovate with each other to promote their services through social media. The research aims to measure how effective the implementation of social media marketing activities is in building brand awareness, brand image, brand equity, and trust from private hospital patients and their influence on visit intention. This study uses quantitative methods, and the data obtained will be processed using CB-SEM with the IBM AMOS application, analyzing 264 questionnaire responses. The study results show that social media marketing activities affect brand awareness, brand image, and trust but do not affect visit intention. Meanwhile, trust and brand equity have a significant impact on visit intentions. However, brand awareness does not affect brand image, yet both significantly impact brand equity. This study shows that collaboration between variables is needed to impact patient visit intentions positively. It is hoped that this research can help the management of private hospitals and other health facilities in forming marketing strategies through social media activities.